Discovery of a multiply lensed submillimeter galaxy in early HerMES Herschel/SPIRE data - Conley, A.; Cooray, A.; Vieira, J.; Solares, E.; Kim, S.; Aguirre, J.; Amblard, A.; Auld, R.; Baker, A.; Beelen, A.; Blain, A.; Blundell, R.; et al. (2011)
We report the discovery of a bright (f(250 μm)>400 mJy), multiply lensed submillimeter galaxy HERMES J105751.1+573027 in Herschel/SPIRE Science Demonstration Phase data from the HerMES project. Interferometric 880 μm Submillimeter Array observations resolve at least four images with a large separation of ~9''. A high-resolution adaptive optics Kp image with Keck/NIRC2 clearly shows strong lensing arcs. Follow-up spectroscopy gives a redshift of z = 2.9575, and the lensing model gives a total magnification of μ ~ 11 ± 1. The large image separation allows us to study the multi-wavelength spectral energy distribution (SED) of the lensed source unobscured by the central lensing mass. The far-IR/millimeter-wave SED is well described by a modified blackbody fit with an unusually warm dust temperature, 88 ± 3 K. We derive a lensing-corrected total IR luminosity of (1.43 ± 0.09) × 1013 L ☉, implying a star formation rate of ~2500 M ☉ yr–1. However, models primarily developed from brighter galaxies selected at longer wavelengths are a poor fit to the full optical-to-millimeter SED. A number of other strongly lensed systems have already been discovered in early Herschel data, and many more are expected as additional data are collected.